2018
DOI: 10.1016/j.jgeb.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture, transformation and genetic fidelity of Milk Thistle

Abstract: This review article presents a consolidated explanation and provides a comprehensive description of various studies, carried out on in vitro culture and hairy root cultures of S. marianum which can be consider an alternative source of flavonolignans. To overcome the constrains of conventional propagation of silybum plant, tissue culture and advanced biotechnology proved to be an influential tool that can complement conventional breeding and accelerate silybum development. The present review is focused on biote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…[34,37]. A lower response of root induction was also observed in PGR-free media similar to that observed for S. marianum [36]. Higher number of roots on Hill's thistle plantlets had no effect on survival as all of the plantlets acclimatized after five days in the mist bed survived.…”
Section: Site Type Name Overwinter Survival (%) Flowering (%) Shoot Rsupporting
confidence: 73%
See 1 more Smart Citation
“…[34,37]. A lower response of root induction was also observed in PGR-free media similar to that observed for S. marianum [36]. Higher number of roots on Hill's thistle plantlets had no effect on survival as all of the plantlets acclimatized after five days in the mist bed survived.…”
Section: Site Type Name Overwinter Survival (%) Flowering (%) Shoot Rsupporting
confidence: 73%
“…Stunted shoots at high concentrations of BA have also been observed in other plant species [35]. With a high concentration of ZEA, shoot proliferation was observed, however, it was not as effective for shoot proliferation in Hill's thistle as it was in other thistle species such as Silybum marianum (L.) Gaertn [36]. The shoots when grown on the medium with an added exogenous auxin (NAA or IBA) led to root induction and whole plantlet development.…”
Section: Site Type Name Overwinter Survival (%) Flowering (%) Shoot Rmentioning
confidence: 87%
“…In another study, the combination of 2,4-D and Kin at 2 mg/L each added in MS media containing and 30 g/L sucrose resulted in optimal callus induction in S. marianum using hypocotyl and cotyledon explants, respectively [35,36]. After optimization of root explants as an appropriate explant and 2,4-D and BA (2 mg/L, each) as a suitable PGRs combination for the callus induction, the root explants mediated calli were incubated on MS media supplied with different concentration of ZnO NPs (0.05, 0.1 and 0.15 mg/L) either alone or in combination with PGRs (2,4-D and BA) and kept under various light condition for callus proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…Due to a small nano size, increased surface area and having a strong potential to move inside the cells through apoplastic or symplastic route ZnO NPs could lead to more electrostatic interactions with the plant cell membranes. Eventually, they activate the pathways for the synthesis of polyphenols and enhance their accumulation in the cell [35].…”
Section: Discussionmentioning
confidence: 99%
“…S. marianum contains a relatively high amount of lipids in the form of triglycerides before processing [ 4 ]; the oil content is about 18%–31% and has plenty of unsaturated fatty acids, especially in the form of linoleic acid (42%–54%) and oleic acid (21%–36%). S. marianum can therefore also be used in human nutrition [ 12 ]. A recent study demonstrated the antatritic and antioxidant effects of milk thistle oil proving the potential to utilize these effects in the food and pharmaceuctical industries [ 13 ].…”
Section: Introductionmentioning
confidence: 99%